High-rate deposition of chromium coatings by magnetron sputtering; Gas Discharge Plasmas and Their Applications (GDP 2019) - Sidelev D. V. Dmitry Vladimirovich; Bleykher (Bleicher) G. A. Galina Alekseevna; Grudinin V. A. Vladislav Alekseevich; Krivobokov V. P. Valery Pavlovich; Bestetti M. Massimiliano (2019, 2019)
Заглавие с титульного экрана